2007
DOI: 10.1007/s10526-007-9111-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of formulation procedures on the effect of the biocontrol agent Serratia plymuthica HRO-C48 on Verticillium wilt in oilseed rape

Abstract: Verticillium wilt is an important disease in oilseed rape with an increasing importance worldwide. Currently, there are no methods available to suppress the pathogen. A biological protection strategy on the basis of the plant-beneficial bacterium Serratia plymuthica HRO-C48 to control Verticillium dahliae in oilseed rape was developed. Three different techniques to apply the biocontrol agent to seeds, namely pelleting, film coating and bio-priming, were evaluated considering the influence on the control activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 31 publications
(27 reference statements)
2
56
0
3
Order By: Relevance
“…Bfreedom^(Seminis, Holland) seeds were surface-sterilized for 5 min using 2 % NaOCl. Bio-priming was performed in accordance with the modified protocol of Müller and Berg (2008). Seeds were immersed in the cell suspension for 4 h at 20°C under agitation.…”
Section: Seed Treatment (Bio-priming)mentioning
confidence: 99%
“…Bfreedom^(Seminis, Holland) seeds were surface-sterilized for 5 min using 2 % NaOCl. Bio-priming was performed in accordance with the modified protocol of Müller and Berg (2008). Seeds were immersed in the cell suspension for 4 h at 20°C under agitation.…”
Section: Seed Treatment (Bio-priming)mentioning
confidence: 99%
“…Seeds were soaked in a bacterial suspension to allow imbibition of water and bacteria into the seed. Bio-priming seeds provided higher control against V. longisporum than coating bacteria on the seed surface (Müller and Berg 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary investigations in laboratory and greenhouse trials revealed that both bacteria have potential to control Verticillium longisporum and L.maculans in the OSR cultivar Talent and in a field trail a significant reduction of L. maculans leaf infection was recorded after seed bio-priming with S. plymuthica (Hammoudi 2007). As S. plymuthica cells survive less well on the outer surface of OSR seeds (Müller and Berg 2008), the authors applied the bacteria by bio-priming. Seeds were soaked in a bacterial suspension to allow imbibition of water and bacteria into the seed.…”
Section: Introductionmentioning
confidence: 99%
“…Potting soil (Einheitserdewerk, Uetersen, Germany) was then mixed with vermiculite and the vermiculitefungal culture at a ratio of 20:5:1 (v/v/v). In healthy controls pots were filled with potting soil mixed with vermiculite (4:1, v/v) (Müller and Berg 2008).…”
Section: Verticillium Longisporum Inoculum Preparation and Soil Infesmentioning
confidence: 99%
“…Both antagonistic bacteria had recently been tested in several OSR cultivars to reduce infection with P. lingam (Abuamsha et al unpublished). Müller and Berg (2008) improved seed treatment techniques for control of V. longisporum with S. plymuthica in greenhouse trials and reported highest control when applying S. plymuthica by bio-priming to OSR seeds. The present study included P. chlororaphis because the existing registration as plant protection product would enable a quicker introduction into practice for this strain than for S. plymuthica, which is not yet registered.…”
Section: Introductionmentioning
confidence: 99%